Nonlinear finite element evaluation of the seismic performance of the historic ayvat masonry weir - Mollamahmutoglu, Cagri; Ozturk, Mehdi; Aksoylu, Ceyhun; Madenci, Emrah; Ozkilic, Yasin Onuralp (SPRINGER, 2026)
A nonlinear seismic assessment of the 18th-century Ayvat masonry weir was performed by integrating three-dimensional finite-element (FE) modeling with Ground-Penetrating Radar (GPR) surveys. A detailed ABAQUS model of approximately 70000 continuum elements was developed and calibrated using laboratory-measured stone-mortar properties and GPR-derived foundation profiles. Nonlinear time-history analyses were carried out under Turkish Earthquake Code (TEC-2018) hazard levels DD1 (2%/50 yr) and DD2 (10%/50 yr) for both principal-axis and 45 degrees-rotated records. Under the 45 degrees-rotated DD1 record (EQ1R), crest-to-base displacements reached up to 0.30 m, and the isolated local maximum damage parameter (PEMAX*) reached 0.47. In contrast, under the 45 degrees-rotated DD2 record (EQ2R), maximum displacements remained below 0.01 m and PEMAX* did not exceed 0.14, thereby preserving global stability while inducing residual strains at the abutments. Stress concentrations were consistently detected at material discontinuities and joint zones. Based on these results, targeted retrofitting measures, including joint reinforcement and localized strengthening, are recommended to ensure the structural safety and preserve the heritage integrity of historic masonry weirs.
Keywords: Ayvat weir; Historic masonry; Nonlinear seismic analysis; GPR-based modeling; Damage-plasticity; Turkish earthquake code; ARCH DAM; STRENGTH; MODEL; Engineering; Geology